Content of mediators of innate immunity in the tears of patients with vascular and neurodegenerative manifestations of diabetic retinopathy - M. P. Ruchkin; E. V. Markelova; G. A. Fedyashev (Медицинская иммунология)
According to the results of recent studies, diabetic retinopathy can be considered not only as a vascular disease, but also as a neurodegenerative process. Study of the composition of the tear fluid is used to assess the state of local immunity in the development of eye diseases. However, studies examining the effect of tear composition in diabetic retinopathy are few. The aim of the study is to determine the levels of IL-1β, IL-10, TGF-β3, MMP-7, TIMP-2, protein S100b, BDNF and NGF in the tear fluid ofpatients with vascular and neurodegenerative manifestations of diabetic retinopathy. The study included 80 patients diagnosed with type 2 diabetes which were divided into 2 groups: the 1st group included 40 patients who had no clinical signs of diabetic retinopathy on the fundus; the 2nd group included 40 patients with initial signs of non-proliferative diabetic retinopathy. All those included in the study were examined on an optical coherent tomograph RTVue-100 (USA); the volume of focal losses of retinal ganglion cells (FLV) was determined. An increase in FLV above the normative base of the device was regarded as an OCT-sign of retinal neurodegeneration. According to the results of OCT, the participants of the first and second groups were additionally divided into 4 subgroups: 1A — patients without vascular changes in the fundus and without OCT signs of retinal neurodegeneration (n = 12); 1B — patients without vascular changes in the fundus and with the presence of OCT signs of retinal neurodegeneration (n = 28); 2A — patients with initial non-proliferative DR and without OCT signs of retinal neurodegeneration (n = 10); and 2B — patients with initial non-proliferative DR and with OCT signs of retinal neurodegeneration (n = 30). The levels of IL-1β, IL-10, TGF-β3, MMP-7, TIMP-2, protein S100 b, BDNF, and NGF in tear fluid were determined by enzyme-linked immunosorbent assay. Levels of IL-1β and IL-10 in tear fluid in all subgroups were comparable to controls throughout the study. TGF-β3 content in the tear fluid of patients in the group with initial signs of non-proliferative DR (group 2) was significantly (p = 0.001) lower compared with control and group 2. However, there was no significant difference (p > 0.05) between subgroups A and B within groups. The concentration of MMP-7 in the tear fluid in all subgroups was significantly lower than in the control (p < 0.05). However, in the subgroups with OCT signs of retinal neurodegeneration (1B and 2B), the deficiency of this metalloproteinase was more pronounced (p = 0.0001). The levels of the neuropeptides under study NGF, BDNF and S100 B in tear fluid did not differ from controls in all subgroups.